The Main Causes of the Rise of Political Islam - مجيد، نارام علي (جامعة واسط - كلية الآداب, 2020)
One of the most controversial topics that are argued about among many scholars nowadays is Political Islam. The significance of this appeared widely after the success of Iranian revolution in the previous century, and then the Soviet Union's breakdown in the beginning of 1990s that flamed the desire for recruiting and supporting Islamists, and the active participating in elections in some Arab and Islamic countries. Despite that, the occurrence of some other factors, in previous century, caused momentum to the appearance of political Islam. Hence, this paper comes to shed light on the most important of those reasons and factors.
يعد موضوع الإسلام السياسي من المواضيع الحية والحساسة التي تطرح اليوم على بساط البحث والتحليل والنقاش، وتتناول من جوانب متعددة وزوايا مختلفة. وقد بدأ الاهتمام بالموضوع منذ انتصار الثورة الإيرانية في نهاية سبعينيات القرن المنصرم، ثم تطور الاهتمام به بعد انهيار الشيوعية في بداية التسعينيات، ومشاركة أحزاب إسلامية في الانتخابات في بعض الدول العربية والإسلامية. ومع ذلك فقد عد الباحثون وقوع بعض الحوادث والوقائع منذ منتصف القرن التاسع عشر كأسباب مؤثرة ورئيسية لظهور الإسلام السياسي، ومن هنا يأتي هذا البحث ليلقي الضوء على أهم تلك الأسباب.
Keywords: الإسلام السياسي -- تاربخ إيران -- القرن التاسع عشر -- الصراعات السياسية